2013
DOI: 10.1038/srep03013
|View full text |Cite
|
Sign up to set email alerts
|

CSF1R mutations in hereditary diffuse leukoencephalopathy with spheroids are loss of function

Abstract: Hereditary diffuse leukoencephalopathy with spheroids (HDLS) in humans is a rare autosomal dominant disease characterized by giant neuroaxonal swellings (spheroids) within the CNS white matter. Symptoms are variable and can include personality and behavioural changes. Patients with this disease have mutations in the protein kinase domain of the colony-stimulating factor 1 receptor (CSF1R) which is a tyrosine kinase receptor essential for microglia development. We investigated the effects of these mutations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 35 publications
3
68
1
Order By: Relevance
“…We suggest that these vascular changes could have altered cerebral blood flow autoregulation resulting in regional ischemia similar to the mechanism proposed for the pathogenesis of leukoaraiosis (23). Therefore, it is possible that CSF1R mutation could set a limit to the degree of microglial proliferation (27), thus setting off events that culminate in the pathologic changes observed in the white matter. Therefore, it is possible that CSF1R mutation could set a limit to the degree of microglial proliferation (27), thus setting off events that culminate in the pathologic changes observed in the white matter.…”
Section: Discussionmentioning
confidence: 56%
“…We suggest that these vascular changes could have altered cerebral blood flow autoregulation resulting in regional ischemia similar to the mechanism proposed for the pathogenesis of leukoaraiosis (23). Therefore, it is possible that CSF1R mutation could set a limit to the degree of microglial proliferation (27), thus setting off events that culminate in the pathologic changes observed in the white matter. Therefore, it is possible that CSF1R mutation could set a limit to the degree of microglial proliferation (27), thus setting off events that culminate in the pathologic changes observed in the white matter.…”
Section: Discussionmentioning
confidence: 56%
“…One critical factor in microglial development and survival is CSFR1. Mice devoid of this receptor do not have microglia (8,20), and mutations that affect the function of the kinase domain of the receptor cause severe neurological syndromes in mice and humans (21)(22)(23)(24). In line with this, in 2014, Elmore et al showed that a chemical inhibitor of CSF1R virtually ablated the microglial population in the healthy brain.…”
Section: Lesson 3 As Long As the Blood-brain Barrier Is Intact Micrmentioning
confidence: 98%
“…Ligand-stimulated CSF-1R kinase activity was abolished for homodimeric receptors bearing each of 15 different missense mutations or each of four aberrant splice variants so far tested [40,41,47,50,51]. However, cotransfection experiments indicate that expression of the mutant chain does not suppress phosphorylation of the wild-type chain [47].…”
Section: Csf1r Mutations Cause Adult-onset Leukoencephalopathy With Amentioning
confidence: 99%